Laughing for Well-Being: Investigating the Impact of Laughter Therapy on Stress Levels among the Elderly Population - Damor, Rahul K. (International Journal of Nursing Research, 2024)
Background: The aim of the study was to evaluate the impact of laughter therapy on the degree of perceived stress experienced by elderly residents of a particular assisted living facility. Methods: A pre-experimental, one-group, pre-test–post-test research design was employed. The technique of purposeful sampling was applied. A selection of thirty samples was made. The study’s participants were senior citizens living in retirement communities in a designated district. Findings: During the pretest, two samples (6.66%) reported low stress, twelve samples (40%) reported moderate stress, and sixteen samples (53.33%) reported high perceived stress. The mean difference was determined to be 11.7, with the mean pre-test score being 26.4 and the mean post-test score being 14.7. It demonstrates that there was a substantial difference between the mean pre-test and post-test scores. Thus, following the application of laughter therapy, the samples’ perceived stress levels decreased. Conclusion: Laughter therapy is beneficial in lowering stress levels in the elderly population, according to this study. Thus, we can conclude that laughter therapy is beneficial for stress relief.